Unhappy Return to Homeland. A Study on the Reasons why Returned Albanian Migrants re-abandon their Country - Osmani, Myslym; Andoni, Mira (Technium Social Sciences Journal, 2022)
This is a study on the tendency and factors of re-leaving of Albanian migrants returned from migration. The study uses data collected through a special survey by INSTAT for 1878 individuals, where the population of interest was that of returned migrants. To conduct the study, the literature desk study, descriptive statistical method, and exponential binomial modeling method are used. The study highlights as the main factors of re-migration of returned migrants the lack of prospects for development of the country, poor economic living conditions, unemployment or few employment opportunities, which result in insufficient income for migrant families. Since some migrants have plans to invest after returning home, other important reasons evidenced by the study are the lack of tax and customs facilities as well as the lack of access to credit. Poor health services and public services in general and poor political stability are other reasons for migration. Persons who are unemployed, as well as persons who were self-employed in the last country of migration, have a stronger tendency for re-migration. The study also highlights the lack of effective policies in support of migrants upon their return and emphasizes the need to involve migrants in drafting the government's political development agendas, which would ensure both faster economic development of the country and more adequate and effective addressing of migration issues.